Avaliação dos efeitos do enriquecimento ambiental no comportamento de camundongos expostos a um modelo de transtorno de estresse pós-traumático - Blanco, Marília Bazan (2015)
A Post Traumatic Stress Disorder (PTSD) may appear after experiencing a stressful situation and is characterized by avoidance of situations that remind the trauma and persistent hyperarousal, and may come associated with anxiety and cognitive disabilities. Although their treatment is usually pharmacological, non-pharmacological interventions has been shown to be effective. While nonpharmacologic strategy, an environmental enrichment (EE) results in decreased anxiety and improving memory in several animal experiments. Thus, this study aimed to evaluate the effects of environmental enrichment on anxiety like behavior and memory in mice submitted to a model of PTSD, with different re-exposure to the situational reminders (1 or 10 minutes). For this, male Swiss mice, exposed or not to environmental enrichment, were submitted to a model of PTSD, in a dark-light box (DL-box). After this aversive procedure (scrambled shock of a 0.5mA and re-exposure to situational reminders), the animals were tested in a DL-box and a modified DL-box (mDL-box), in an elevated plus maze (EPM) and to a new object recognition test. The results demonstrated that, in non-enrichment animals, aversive stimulation without situational reminders increased anxiety like behaviors and traumatic memory in DL-box, but not in the mDL-box. Aversive stimulation with situational reminder of one minute increased anxiety like behaviors and traumatic memory in DL-box, in mDL-box and in EPM, while the aversive stimulation with 10 minutes situational reminders reduced anxiety like behaviors and traumatic memory. Environmental enrichment attenuated the effects of the shock. On groups with situational reminders of one minute, environmental enrichment did not change anxiety like behaviors and memory but reverted the sensitization in the EPM, and on groups with one-minute situational reminders, resulted in increased anxiety like behaviors and traumatic memory in DL-box, as well as decrease in total entries in the dark side of mDL-box. These results suggest that re-exposure to situational reminders of one-minute increases anxiety like behaviors and induces behavioral sensitization, furthering reconsolidation of traumatic memory, while reexposure to 10 minutes situational reminders results in reduced anxiety like behaviors and extinction of traumatic memory. Further, environmental enrichment has not been able to mitigate the effects induced by re-exposure to one-minute situational reminders on traumatic memory, and favored the maintenance of traumatic memory, even when animals are re-exposed to situational reminders for 10 minutes, damaged their extinction, but reversed the effects of this procedure in behavioral sensitization. Thus, the effects of the environmental enrichment on the proposed model of PTSD are complex, and depend on the length of the situational reminders and the behaviors that are evaluated